Risk Management, Capital Adequacy and Audit Quality for Financial Stability: Assessment from Commercial Banks of Pakistan - Kamran, Hafiz Waqas; Omran, Abdelnaser; Mohamed-Arshad, Shamsul Bahrain (Asian Economic and Financial Review, 2019)
The purpose of this study is to examine the effect of bank-based risk measures, country related and international risk factors along with capital ratio and audit quality for stability measures. This article has filled the literature gap while addressing two financial stability measures: Z score through return on assets and return on equity (ZROA and ZROE). A sample of 28 commercial banks is collected from national financial market in Pakistan, with annual observations each year from 2007 to 2016. Panel regression models like ordinary least square (OLS), fixed effect and random effect under robust title are applied to examine the effect of risk factors, capital ratio and audit quality on financial stability (FS). Study finds that bank-based risk factors such as liquidity, credit and operational risk have significant negative influence on both stability measures. Excessive capital ratio seems also to adversely affect financial stability measures. Additionally, higher payments to auditors increases audit quality, resulting in a positive influence on both stability measures. Policy makers, financial analysts and credit officers in banks recommend analysis and review of the relationship between risk factors, capital ratio and audit quality, and the FS of Pakistani commercial banks. However, this work is limited to commercial banks, with no consideration of developed financial institutes and industrial banks. Additionally, there is no methodological application of advanced techniques like GMM.